Characteristics of voltage sags in power systems - Mohd Faizal Amril (School of Electrical System Engineering, University Malaysia Perlis, 2011)
Voltage sags are the short durations in root-mean-square (RMS) rated AC voltage occur during faults may cause miss-operations to the customers equipment and loads of power system and recognized as the most important power quality problem. However, this thesis investigates the sag event which is caused by a short circuit or fault to the three-phase transmission line. This thesis also presents the comparisons between voltage reductions at two Bus terminals for three-phase systems where the difference in voltage drop or reduction is caused by the transformer connection and also because of the type of fault caused. Simulations were carried out using PSCAD software which it is based on a number of configurations which has been modeled. The systems used in this thesis are two Bus transmission line systems. Simulation results indicate that three-phase line has a low voltage reduction at second bus terminal compared with the first Bus terminal due to the two-phase to ground fault. This is dependent on the transformer used in the circuit either step-up or step-down transformer. Short circuit or fault occurring on the second Bus terminal causing of the voltage decreased in the terminal of induction motor and increased induction motor current at the motor terminal.